'Genuine' religions and their arena of legitimation in Italy – the role of the ECtHR. Issue 3 (2nd October 2017) - Giorgi, Alberta; Annicchino, Pasquale
ABSTRACT: In this contribution, we address the everlasting debate on the definition of religion from a multiscalar perspective. Supranational courts – and, especially, the European Court of Human Rights – gained a major legitimising role in this respect. One may thus expect that religious minorities with uncertain status look at supranational courts as attractive and favourable venues. The 'local' must be taken into account, too, in the complex government of religious diversity: decentralised policies and different religious profiles make room for adapting the treatment of religious minorities at the local level, especially in situations characterised by the absence of a legal national framework. Grounded on an analysis of national and international case law, and on interviews addressing the representatives of religious minorities, our contribution explores the multiscalar repertories of action of religious minorities in pursuing the official recognition and the protection of their religious rights.